Cannabidiol in the management of in-patient cannabis withdrawal: clinical case series. (August 2017) - Pokorski, Izabella; Clement, Nicole; Phung, Nghi; Weltman, Marin; Fu, Shanlin; Copeland, Jan
Aim: To assess the feasibility of the use of cannabidiol (CBD) for the management of cannabis withdrawal.Patients & methods: Eight participants were admitted to an in-patient detoxification facility for a 7-day open-label trial of CBD. Five participants received 600 mg of CBD and three participants received 1200 mg of CBD. Participants returned for a 28-day follow-up interview.Results & conclusion: CBD was well tolerated by all participants. Five completed the full treatment period and abstinence was maintained by four participants at day 28 follow-up. All those receiving the higher dose completed treatment and achieved abstinence at follow-up. This pilot study suggests that further exploration of CBD as a pharmacological adjunctive therapy for cannabis withdrawal and dependence is warranted. Registration ACTRN1261400024866.